Improving management of enterprises based on corporate governance (Journal of Universal Science Research, 2024)
The aim of this research is to inspect whether Corporate Governance (CG) attributes such as Audit Meeting Frequency, Ownership Concentration, Board Meeting Frequency, Foreign Ownership, Institutional Ownership, Board Gender Diversity, Audit Committee Size, Board Size, Audit Reputation and CEO Compensation affect firms’ performance in every where. This research employed the pooled least square method to estimate the association among attributed of CG and firm performance measures (Return on Asset and Tobin’s Q) by selecting the Cement Sector and Energy sector companies listed in Pakistan Stock Exchange (PSX) during 2009–2022. A substantial result is that the energy sector’s CG system does not differ from the cement sector. Tobin’s Q is lesser than ROA, suggesting the same condition as companies in the cement sector. On average, firms in the energy sector are older than the firms in the cement sector. It contradicts the result of profitability proxies of the energy sector. Being older firms, the profitability proxies show lower returns as compared to cement sector firms.